Cretaceous-Paleocene Biostratigraphy of Jardas Al Abid Area, Al Jabal Al Akhdar, NE Libya - I. Obaida, Motasem; O. Abdulsamad, Esam; M. Muftah, Ahmed; K. Khalifa, Ali (Scientific Journal of University of Benghazi, 2025)
ABSTRACT This study focuses on the biostratigraphy of the Cretaceous (Albian–Maastrichtian) and Paleocene (Danian) sequences exposed in both surface and subsurface sections of the Jardas al’Abid area, Al Jabal Al Akhdar, northeastern Libya. The investigation is based on systematically collected samples from four outcrop sections and one subsurface borehole (Water well). A total of thirty foraminiferal and five molluscan species were identified. Based on the vertical distribution of planktic foraminifera, nine biozones have been established in descending order: Parvularugoglobigerina Eugubine (Danian), Dicarinella concavata (Coniacian), Whiteinella brittonensis (Early Turonian), Hedbergella spp.–Pithonella spp. (Late Cenomanian), Rotalipora cushmani (Late Cenomanian), Thalmanninella brotzeni (Early Cenomanian), Biticinella breggiensis, Pseudothalmanninella ticinensis (Late Albian), and Ticinella primula (Middle Albian). Additionally, three molluscan biozones have been identified: Mecaster batnensis, Costagyra olisiponensis (both Late Cenomanian), and Inoceramus (Endocostea) balticus (Campanian), along with one ammonite biozone, Kitchinites emscheris (Early Santonian). This work represents the most detailed foraminiferal biostratigraphic framework for the region to date, with several of the proposed biozones being reported from Al Jabal Al Akhdar for the first time. The established biozones show a strong correlation with those of neighboring countries as well as with Mediterranean coastal regions of Europe, reinforcing the regional biostratigraphic continuity across the southern Tethyan margin. A new discovery of existing Paleocene (Danian) strata has been confirmed at the Jardas al’Abid area.